IS skills for IT professionals in Malaysia / Murugan Nadarajah - Murugan , Nadarajah (2007)
This study was undertaken to compile data about the IS skills for the IT professionals in Malaysia and also to describe what type of skills that the IT professionals in Malaysia should have for their career advancement. This study discusses about the important skills for certain specific post and the changes that must be done in Computer Science and IT curriculum so that IT graduates would be able to acquire appropriate skills needed by industry. The study used a survey research method and a set of questionnaire was administered to 150 IT professionals in Klang Valley. The findings revealed that well rounded IT professional should have a combination of Analysis and Design Skills, Business Skills and Interpersonal Skills. Most of the respondents acquired these skills through their working experience since most of university and college curricular does not provide them with these skills. Overall the skill levels of IT professionals on each skill depends on their position, knowledge they acquired while studying in universities and colleges and also through their working experience. Since, there is no proper tool to evaluate the IS skills among the employees in IT field, a proper system was therefore needed to evaluate the IS skills among IT professional. In this way employees can be aware of their skill level and take further action to improve it. In order to do that, Information System Skills Assessment System (ISSAS) was developed.